Effect of Round Robin strategy in achievement of sciences of Second intermediate Grade Female students - ayal mater, Firas; Nassir Hussein, Hanan (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to identify the effect of Round Robin strategy on the achievement of science subject of second intermediate grade students, to achieve this aim, Round Robin strategy was adopted. The research sample reached (56) students , (28) students at the experimental group that is studied according to Round Robin strategy and (28) students in the control group who studied according to usual method, after completing the experiment, the final achievement test was applied, (t-test) was used as statistical processing the data it was found that there was a statistical significant difference in the achievement test for the benefit of the experimental group in the science subject due to the application of the Round Robin strategy .